Numerical study of evaporation‐induced salt accumulation and precipitation in bare saline soils: Mechanism and feedback. Issue 10 (18th October 2014) - Zhang, Chenming; Li, Ling; Lockington, David
Abstract Evaporation from bare saline soils in coastal wetlands causes salt precipitation in the form of efflorescence and subflorescence. However, it is not clear how much the precipitated salt in turn affects the water transport in the soil and hence the evaporation rate. We hypothesized that efflorescence exerts a mulching resistance to evaporation, while subflorescence reduces the pore space for water vapor to move through the soil. A numerical model is developed to simulate the transport of water, solute, and heat in the soil, and resulting evaporation and salt precipitation with the hypothesized feedback mechanism incorporated. The model was applied to simulate four evaporation experiments in soil columns with and without a fixed shallow water table, and was found to replicate well the experimental observations. The simulated results indicated that as long as the hydraulic connection between the near surface soil layer and the water source in the interior soil layer exists, vaporization occurs near the surface, and salt precipitates exclusively as efflorescence. When such hydraulic connection is absent, the vaporization plane develops downward and salt precipitates as subflorescence. Being more substantial in quantity, efflorescent affects more significantly evaporation than subflorescence during the soil‐drying process. Different evaporation stages based on the location of the vaporization plane and the state of salt accumulation can be identified for characterizing the process of evaporation from bare saline soils with or without a fixed shallow water table.